Pengendalian Persediaan Oli di PT. XYZ dengan Menggunakan Metode Analisis ABC - Basir, Muh; Sarungu, Selvia; Iskandar, Raden Andang (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT. XYZ is a company that supplies lubricants and fuel for both the automotive and mining industries. This research examines oil inventory control in the warehouse. PT. XYZ using the ABC Analysis method. Previously PT. XYZ does not yet use the ABC Analysis method in inventory control. The aim of this research is to find out how to control oil supplies at PT. XYZ and to find out oil inventory control at PT. XYZ using the ABC Analysis method. Then the results of this research have found three groups which fall into categories A, B, and C. The type of oil that falls into category A has a total rupiah value absorption of Rp. 4,878,859,430 or equal to 70.28% of the total rupiah value, which consists of 6 types of oil or equal to 13.23% of the total of all types of oil. Then the type of oil that falls into category B has a total rupiah value absorption of Rp. 1,351,126,100 or the same as 19.46% of the total rupiah value, which consists of 6 types of oil or the same as 22.44% of the total of all types of oil. And the type of oil that falls into category C has a total rupiah value absorption of R. 712,058,180 or the same as 10.26% of the total rupiah value, which consists of 15 types of oil or the same as 64.33% of the total of all types of oil.